Analysis Prospective Mathematics Teachers’ Lesson Planning: A Praxeological-Didactical Theory - Musyrifah, Eva; Suryadi, Didi; Cahya, Endang; Dahlan, Jarnawi Afgani (Southeast Asian Mathematics Education Journal, 2024)
A high quality of lesson planning is the key to achieving effective learning. One of the characteristics of effective learning is that it minimizes learning obstacles. This study aims to explore an Indonesian prospective mathematics teacher’s lesson planning and identify its learning obstacles. Data was analyzed from the lesson plan document of prospective mathematics teacher students carrying out teaching practices at one of the high schools in Jakarta. Analysis was done using the praxeological-didactical (PDA) method. PDA offers space to analyze human actions, such as lesson plans. Four types of tasks are presented in the lesson plan on drawing graphs of quadratic functions.  The predicted learning obstacles identified from the lesson plan are (1) epistemological obstacles, caused by the limitations of certain contexts; (2) ontogenic obstacles, caused by the presentation of tasks due to inappropriate prerequisites; and (3) didactic obstacles, caused by tasks that are not relevant to the next task.  The implication is that the results of the study can be used to improve a quality lesson plan, and the use of a PDA can be a consideration for prospective mathematics teachers when designing a quality lesson plan.